Clinical correlations with EGFR circulating tumor DNA testing in all-stage lung adenocarcinoma - Incharoen P. (2023)
BACKGROUND: Information on genetic alterations, notably EGFR mutations, is important for guiding non-small-cell lung cancer (NSCLC) treatment. Circulating tumor DNA (ctDNA) analysis represents a less invasive alternative to tissue biopsy for analyzing mutation status, but its clinical value may vary across disease stages. OBJECTIVE: To explore clinical correlates of ctDNA and tissue/plasma-based EGFR mutation (EGFRm) status across all NSCLC stages. METHODS: Ninety patients were analyzed, representing three cohorts: newly-diagnosed early-stage, advanced-stage, and recurrent NSCLC. Relationships among clinical/surgical parameters, ctDNA, EGFRm status, and survival outcomes were analyzed. RESULTS: Plasma/tissue EGFRm concordance was lower in early-stage (58.6%) than in advanced-stage patients (87.5%). In early-stage patients, ctDNA levels were variable and not significantly associated with clinical/surgical parameters. In advanced-stage patients, time to EGFR-TKI treatment failure (TTF), but not overall survival (OS), was significantly longer in EGFRm-positive vs. EGFRm-negative patients. In patients with recurrent disease, 40% of plasma samples were EGFRT790M-positive at recurrence. In T790M-positive patients, we noted slight trends toward longer OS with vs. without osimertinib treatment and longer OS and TTF with second-line vs. later-line osimertinib. CONCLUSIONS: Our results affirm the use of ctDNA testing in advanced-stage and recurrent NSCLC. Further studies on osimertinib as early-line therapy, clinical correlates and the utility of plasma-based testing in early-stage NSCLC are warranted.